Evaluación clínica y radiográfica de autotrasplantes y reposiciones dentales - Gloria Jeanethe Alvarez-Gomez; Rodrigo Felipe Naranjo-Restrepo; Claudia Liliana Pérez-Pardo (Revista Facultad de Odontología Universidad de Antioquia, 1996)
Eight autotransplants and two dental repositions were evaluated prospectively. The patients, who has consulted from august1994 to apri11996, were recruited _from the stomatology- unit of the San vicenthospital. The follow up of these patients was held for a period of one year. The following clinical and radiographic parameters were evaluated; pain, color change, bleeding movili0i-, space of periodontal ligament, inner and outerressorption, cameral obliteration and stage of radicvlar development. There were various donant teeth and different receptor sites. The most frequent autotransplant was done using third molars to replace first molar teeth. The repositions were done in the premolar area. The survival rate was 100% to six months and 75% to twelve months. All the patients did not complete the control period. One for the autotrasplants was lost despite the pulp treatment done with calcium hydroxide. The initial results in this pilot study show that autotransplants and dental repositions are important treatment alternatives with a high percentaje of success, in patients with tooth decay or alteration in the eruption by malpositions.